The comparison between health literacy and quality of life in three groups of mothers with cerebral palsy, Autism and intellectual impairments - Anahita Khodabakhshi-Koolaee; Hanieh Rostami Goharni; Atuosa Kafashpour Marandi (Mashhad University of Medical Sciences, 2018)
Background and objective: disability of children has multiple negative impacts on psychological and social on mothers. The study of health literacy in mothers with children with special needs and the impact of the health literacy on quality of life is necessary. The aim of this study was to compare the health literacy and quality of life in three groups of mothers including; Cerebral palsy, Autism, and intellectual impairments. Methods: The research method of this study was ex-post design. The statistical society of present study was all of the mothers with special needs care referred to rehabilitation centers in the west region of Tehran city by 2016. The samples of research were dividing into three groups (each group was 40 mothers). All of the participants were 120 mothers selecting by simple sampling method. For gathering data using the Health Literacy Questionnaire for Adults (HELIA) and World Health Organization Questionnaire of Quality of Life (WHOQOL). The data were analyzed by ANOVA and with SPSS software version 21. Results: The results indicated that three groups of mothers had a significant difference in health literacy and sub-scales of the questionnaire (p<0/05). The mothers with Autism child had more scores than other two groups. However, the quality of life scores had not shown the significant difference in three groups expect the two scales psychological and physical health (P>0/05). Conclusion: The findings revealed that the study of health literacy was the impact of quality of life of mothers. Therefore, the educational and awareness programs seem to be urgent for improving the health literacy and quality of life in three groups of mothers and considering by health professionals.  Paper Type: Research Article.